2017
DOI: 10.1155/2017/4139656
|View full text |Cite
|
Sign up to set email alerts
|

Serology of Viral Infections and Tuberculosis Screening in an IBD Population Referred to a Tertiary Centre of Southern Italy

Abstract: Background With the introduction of more potent immunosuppressive agents in inflammatory bowel disease, prevention of opportunistic infections has become necessary by introducing screening programs. Prevalence of the most important infectious agents may vary in different geographical areas. The aim of our study was to assess the immune status for hepatitis B, varicella, mononucleosis, and cytomegalovirus infection together with the determination of the hepatitis C and tuberculosis status in Southern Italy. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Key evidence: Data were available from 10 cross-sectional studies. [39][40][41][42][43][44][45][46][47][48] Although older studies in Western countries showed a higher prevalence of past hepatitis B virus (HBV) infection among patients with IBD compared to the general population, this is not reported in more recent studies. In Eastern countries where HBV is endemic, the prevalence rates of past HBV among patients with IBD appeared to be higher than in the general population.…”
Section: Hepatitis Bmentioning
confidence: 99%
“…Key evidence: Data were available from 10 cross-sectional studies. [39][40][41][42][43][44][45][46][47][48] Although older studies in Western countries showed a higher prevalence of past hepatitis B virus (HBV) infection among patients with IBD compared to the general population, this is not reported in more recent studies. In Eastern countries where HBV is endemic, the prevalence rates of past HBV among patients with IBD appeared to be higher than in the general population.…”
Section: Hepatitis Bmentioning
confidence: 99%
“…Among these, 17 studies were prospective [18][19][20][21][22][23][24][25]30,31,34,39,45,[48][49][50][51] and 17 were retrospective in nature. [26][27][28][29]32,33,[35][36][37][38][40][41][42][43][44]46,47 The majority of the studies were from Europe 18,20,[24][25][26][27]31,34,36,39,40,47,49 and Asia. 28,30,33,35,37,…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…28,30,33,35,37,38,41,42,45,46,51 The number of patients in the studies varied from 74 to 5,096 with a mean age from 32.9 to 50.8 years. Majority of the studies included consecutive patients with IBD while 7 studies 20,29,31,34,36,40,44 analyzed data of patients being planned for biologicals. Prior risk factors for viral hepatitis and vaccination history were reported in 9 studies 21,25,26,30,31,33,38,43,51 and 10 studies, 25,30,31,33,34,37,39,41,45,49 respectively.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations